Penanaman Modal Pada Sektor Ketenagalistrikan yang Dikuasai Negara Berdasarkan Undang-Undang Penanaman Modal - Ashilah, Afganovic Mujadid (Jurnal Ilmiah Global Education, 2024)
The issuance of the Job Creation Law has had an impact on investment in the electricity sector in Indonesia. This impact has resulted in changes to business fields or types of businesses previously in the electricity sector for foreign investors requiring certain requirements to be met. However, with the issuance of the job creation law, foreign investors were given the opportunity to invest as much as possible in the electricity sector and were even given incentives; this opportunity was also felt by domestic investors. This role needs to be balanced with the presence of the state, which has so far been carried out by the state in the electricity sector, with the presence of PLN, which provides electricity to the community. With a doctrinal approach, this research links previous research related to investment in national treatment principles and investment in the electricity sector. In this article, we analyze investment regulations in the state-controlled electricity sector based on investment laws, which in conclusion is investment controlled by the state by PLN in the context of providing electricity to the public, but the private sector (Foreign Investment and Domestic Investment) participates in supporting the provision made by PLN